The Criteria For Improvement In The CBT Treatment Of Panic Disorders - Jurin, Tanja (2007)
Introduction: CBT treatment is recognized as a successful approach to panic disorders. According to the CBT model, panic attacks (PA) are consequences of catastrophic interpretations of body sensations. Maintenance of the disorder is supported by avoidant behavior(s) and safety maneuvers. The treatment is usually focused on cognitive restructuring (beliefs, expectations, overestimated appraisal of threat) and on restoring the control over physical arousal. Aim: The aim of this study is to determine relevant criteria for improvement in CBT treatment. Method: At the beginning of the treatment several measures were included in the assessment of improvement of treatment ; structured and semistructured interviews, behavior tests, self-reported measures (Anxiety Sensitivity Index - ASI), self-monitoring (frequency and intensity of panic attacks, number and sort of avoidant and safety behaviors), cognitive components (belief, expectations and estimation of danger) as well as subjective evaluation of how panic interferes with the patient's/client's social and working functioning. Current study is in progress. Panic patients that meet DSM-IV criteria for Panic disorder participate in the study. The case example: Female (35) developed panic disorder shortly after anaphylactic shock due to antibiotic (Cefaleksin). Her worries were as follows: “ What if I get sick and I have to take the drug.” , “ What if I eat something and that could be allergenic for me.” , “ What if I faint and the helpers don’ t know that I’ m allergic to Cefaleksin.” Avoidant behaviors were spreading and generalized. She didn't go anywhere with her children alone, was refusing to take any sort of drugs, didn't want to try new food and had a permanent fear of new panic attacks. Safety behaviors were: carrying an adrenalin injection, inability to stay alone with her children. Through the course of the treatment (10 sessions + 2 follow up sessions) several behavioral techniques (behavior experiments, exposure, self-monitoring, relaxation, attention distraction through the activity) and cognitive interventions (reinterpretation of body sensations, changing metacognitive beliefs about a threat) were applied. The changes after 10 sessions: 1. Release of avoidant behaviors and safety behaviors 2. Decrease in the number, intensity and duration of panic attacks 3. Decrease in fear of fear 3. Significant changes in metacognitive beliefs about threat and her vulnerability 4. Significant decrease in self - report measure results (ASI). From the 56 points at the beginning to 21. 5. Gradually more appropriate functioning Conclusion: Several criteria are included in evaluation of treatment effects: frequency, intensity and duration of panic attacks as well as fear of fear, number and sort of avoidant and safety behaviors, results on self-reported measures, changes in metacognitive beliefs and adequate working and social functioning.